PENGUKURAN FAKTOR RISIKO KETIDAKPATUHAN PENGOBATAN TUBERCULOSIS KHUSUSNYA HEALTH SYSTEM PADA PASIEN PINDAHAN - Leonov Rianto; Siti Aisyah; Ika Agustina (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
During the Covid-19 pandemic, there was a transfer of TB patient referrals from other health facilities to The X Hospital which took effect in April 2020. One of the five factors that caused non-compliance with treatment was the health system. The sub factor included in this is Health facility. The transfer of patient referrals is predicted to be associated with the success rate of TB treatment. This study aims to describe the health system risk factors for non-adherence to treatment of drug-resistant TB (RO) patients. This study uses a quantitative descriptive approach. The population in this study were RO TB patients. The sampling technique is total sampling. The inclusion criteria in this study were RO TB patients whose treatment period was > 6 months and there had been a transfer of health facilities to the Cempaka Putih Islamic Hospital. The total sample obtained is 35 respondents. The results showed that the health system risk factor for non-adherence to treatment of Drug Resistant TB (RO) patients was low because patients did not experience problems in terms of distance to health facilities and competent health workers in providing information about treatment for RO TB patients.